The maize PIN gene family of auxin transporters - Cristian eForestan; Silvia eFarinati; Serena eVarotto (Frontiers in Plant Science, 2012)
Auxin is a key regulator of plant development and its differential distribution in plant tissues, established by a polar cell-to-cell transport, can trigger a wide range of developmental processes. A few members of the two families of auxin efflux transport proteins, PIN-formed (PIN) and P-glycoprotein (ABCB/PGP), have so far been characterized in maize. Nine new Zea mays auxin efflux carriers PIN family members and two maize PIN-like genes have now been identified. Four members of PIN1 (named ZmPIN1a–d) cluster, one gene homologous to AtPIN2 (ZmPIN2), three orthologs of PIN5 (ZmPIN5a–c), one gene paired with AtPIN8 (ZmPIN8), and three monocot-specific PINs (ZmPIN9, ZmPIN10a and b) were cloned and the phylogenetic relationships between early land plants, monocots and eudicots PIN proteins investigated, including the new maize PIN proteins. Tissue-specific expression patterns of the twelve maize PIN genes, two PIN-like genes and ZmABCB1, an ABCB auxin efflux carrier, were analyzed using semi-quantitative RT–PCR. ZmPIN gene transcripts have overlapping expression domains in the root apex, during male and female inflorescence differentiation and kernel development. However, some PIN family members have specific tissue localization: ZmPIN1d transcript marks the L1 layer of the SAM and IM during the flowering transition and the monocot-specific ZmPIN9 is expressed in the root endodermis and pericycle. The phylogenetic and gene structure analyses together with the expression pattern of the ZmPIN gene family indicate that subfunctionalization of some maize PINs can be associated to the differentiation and development of monocot-specific organs and tissues and might have occurred after the divergence between dicots and monocots.